Identification of new potential downstream transcriptional targets of the strigolactone pathway including glucosinolate biosynthesis. (19th March 2023) - Hellens, Alicia M.; Chabikwa, Tinashe G.; Fichtner, Franziska; Brewer, Philip B.; Beveridge, Christine A.
Abstract: Strigolactones regulate shoot branching and many aspects of plant growth, development, and allelopathy. Strigolactones are often discussed alongside auxin because they work together to inhibit shoot branching. However, the roles and mechanisms of strigolactones and how they act independently of auxin are still elusive. Additionally, there is still much in general to be discovered about the network of molecular regulators and their interactions in response to strigolactones. Here, we conducted an experiment in Arabidopsis with physiological treatments and strigolactone mutants to determine transcriptional pathways associated with strigolactones. The three physiological treatments included shoot tip removal with and without auxin treatment and treatment of intact plants with the auxin transport inhibitor, N ‐1‐naphthylphthalamic acid (NPA). We identified the glucosinolate biosynthesis pathway as being upregulated across strigolactone mutants indicating strigolactone–glucosinolate crosstalk. Additionally, strigolactone application cannot restore the highly branched phenotype observed in glucosinolate biosynthesis mutants, placing glucosinolate biosynthesis downstream of strigolactone biosynthesis. Oxidative stress genes were enriched across the experiment suggesting that this process is mediated through multiple hormones. Here, we also provide evidence supporting non‐auxin‐mediated, negative feedback on strigolactone biosynthesis. Increases in strigolactone biosynthesis gene expression seen in strigolactone mutants could not be fully restored by auxin. By contrast, auxin could fully restore auxin‐responsive gene expression increases, but not sugar signaling‐related gene expression. Our data also point to alternative roles of the strigolactone biosynthesis genes and potential new signaling functions of strigolactone precursors. In this study, we identify a strigolactone‐specific regulation of glucosinolate biosynthesis genes indicating that the two are linked and may work together in regulating stress and shoot branching responses in Arabidopsis. Additionally, we provide evidence for non‐auxin‐mediated feedback on strigolactone biosynthesis and discuss this in the context of sugar signaling.